ASSOCIATION OF HEAVY METAL POLLUTANTS IN SOIL, PLANTS, AND WATER WITH TYPE AND DENSITY OF AUTOMOBILES IN LAHORE (Journal of Medical & Health Sciences Review, 2025)
This study investigates the correlation between the type and density of automobiles and the concentrations of heavy metals in soil, water, and plant samples collected from selected areas of Lahore, Pakistan. The research focused on four heavy metals: Lead (Pb), Nickel (Ni), Chromium (Cr), and Cadmium (Cd). Notably, cadmium was consistently absent across all samples. The highest concentrations of Pb, Ni, and Cr were detected in areas with high traffic density, particularly those frequented by heavy-duty vehicles such as trucks and buses. Water samples from high-traffic areas showed significantly elevated levels of Pb, whereas Cr was dominant in areas with moderate traffic, and Ni peaked in locations with the highest vehicle flow. A strong association was found between soil contamination and the accumulation of metals in plant roots and leaves, suggesting active uptake. These findings highlight the pressing need for urban pollution control, especially in megacities like Lahore where vehicular emissions pose a serious environmental and public health threat.